A small molecule inhibitor for phosphatase and tensin homologue deleted on chromosome 10 (PTEN) - Rosivatz,E; Matthews,JG; McDonald,NQ; Mulet,X; Ho,KK; Lossi,N; Schmid,AC; Mirabelli,M; Pomeranz,KM; Erneux,C; Lam,EW; Vilar,R; et al. (ACS Chem.Biol., 2006)
Phosphatase and tensin homologue deleted on chromosome 10 (PTEN), a phosphoinositide 3-phosphatase, is an important regulator of insulin-dependent signaling. The loss or impairment of PTEN results in an antidiabetic impact, which led to the suggestion that PTEN could be an important target for drugs against type II diabetes. Here we report the design and validation of a small- molecule inhibitor of PTEN. Compared with other cysteine-based phosphatases, PTEN has a much wider active site cleft enabling it to bind the PtdIns(3,4,5)P3 substrate. We have exploited this feature in the design of vanadate scaffolds complexed to a range of different organic ligands, some of which show potent inhibitory activity. A vanadyl complexed to hydroxypicolinic acid was found to be a highly potent and specific inhibitor of PTEN that increases cellular PtdIns(3,4,5)P3 levels, phosphorylation of Akt, and glucose uptake in adipocytes at nanomolar concentrations. The findings presented here demonstrate the applicability of a novel and specific chemical inhibitor against PTEN in research and drug development